SYMBOLISM OF MANDALA IN VISUAL ART FORM BASED ON HINDUISM SPIRITUAL - JACKLIN ROSE, NATHAN (Perpustakaan Tun Abdul Rahman Ya’kub (PeTARY), 2018)
This reseach explains the Symbolism of Mandala in Visual Art Form Based on Hinduism Spiritual. It is been carried out by identifying the symbolism and implement it in personal artwork. Mandala Sri Yantra is Spiritual symbol which originally 2 Dimensional and used for spiritual hinduism purposes especially devotion. Sri Yantra also represent the temples blueprint where it accurate the ocation of the goddess in the center of the temple. This project will be new insight for existed knowledge on mandala especially from visual arts perspective